2008
DOI: 10.1007/s00213-008-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allopregnanolone on the reinstatement of cocaine-seeking behavior in male and female rats

Abstract: These findings suggest that ALLO may explain part of PROG's inhibitory effect on cocaine-primed reinstatement, and it may serve as a novel approach for preventing relapse in female cocaine abusers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 69 publications
12
66
2
Order By: Relevance
“…Thus, similar to female rats, drug-experienced women appear to devalue food (and perhaps other natural reinforcers) relative to taking drugs to a greater extent than men, which is likely a significant contributor to the more severe profile of cocaine dependence that women display. Future projects are required to assess the role of estrogen in cocaine choice in a more detailed fashion, as well as examine the effect of other ovarian hormones (eg, progesterone and its metabolite, allopregnanolone) on cocaine choice, as this ovarian hormone has been shown to decrease motivation for cocaine in single reinforcer studies (Feltenstein et al, 2009;Anker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar to female rats, drug-experienced women appear to devalue food (and perhaps other natural reinforcers) relative to taking drugs to a greater extent than men, which is likely a significant contributor to the more severe profile of cocaine dependence that women display. Future projects are required to assess the role of estrogen in cocaine choice in a more detailed fashion, as well as examine the effect of other ovarian hormones (eg, progesterone and its metabolite, allopregnanolone) on cocaine choice, as this ovarian hormone has been shown to decrease motivation for cocaine in single reinforcer studies (Feltenstein et al, 2009;Anker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…With limited access to intravenous cocaine self-administration, female rats show more nonreinforced responding and a prolongation of extinction Fuchs et al, 2005;Kosten and Zhang, 2008). Under similar conditions, female rats also responded more to cocaine-induced reinstatement (Lynch and Carroll, 2000;Anker et al, 2009). In studies that used prolonged access to cocaine (24-hour access in discrete trials), female rats also showed enhanced responding on a progressive-ratio schedule during reinstatement after abstinence without extinction compared with males (Lynch and Taylor, 2004).…”
Section: Sex Differences In the Preoccupationmentioning
confidence: 99%
“…Progesterone and allopregnanolone (the levels of which are low during the estrous phase in rats) both selectively blocked cocaine-primed reinstatement only in female rats, and the effects of progesterone were blocked by finasteride, a drug that blocks the conversion of progesterone to allopregnanolone (Anker et al, 2009), suggesting a role for progesterone in drug-primed cocaine reinstatement. Estradiol, in contrast, increased cocaine-primed reinstatement in limited-access conditions .…”
Section: Effects Of Hormones During the Reproductive Cycle In Femamentioning
confidence: 99%
“…In ovariectomized rats, progesterone inhibited estradiol enhancement of acquisition of cocaine self-administration (Jackson et al, 2006). Both progesterone and its major metabolite, allopregnanolone, blocked reinstatement of cocaine self-administration (Anker et al, , 2009, as well as escalation of cocainemaintained responding ; see for a review, Anker and Carroll, 2010).…”
Section: Introductionmentioning
confidence: 99%